Estudio de factibilidad para la creación de una empresa productora de infusiones a base de la pulpa de café en el cantón Palanda y su comercialización en la ciudad de Loja - Abad Abad, Celinda Marlene (2019)
Excess coffee consumption produces different health consequences by the high content of caffeine, so that over time this has caused search and new healthier beverages with a lower risk of impairment to health. To deal with this situation has been considered an aromatic drink derived from the pulp of the coffee making, in presenting several benefits such as; stressful anti, anti diabetic, protein content, and contains a low percentage of caffeine. On this basis was born the idea of creating a company producer and marketer of herbal teas-based coffee pulp, this in order to contribute in a way positive with the Elimination of diseases caused with drinks that damage the body of the population from which the with total, as well as obtain an economic benefit. For the development of the project was taken into consideration as a main objective: to determine the feasibility for the creation of a producer of herbal teas based on the coffee pulp Palanda canton and its marketing in the city of Loja, in relation to the analysis of the specific objectives such as: Perform market research to learn the terms of offer and demand, the characteristics of the price, what consumers expect from our product and identify the channels of communication that served to promote the product, using the market research, designed for the economic life; prepare a technical study to determine the location, size, project engineering, as well as the organizational design of the company; a financial study to determine the investment and financing of the project, as well as the budgets of costs and income and financial statements; Finally the financial assessment for the feasibility or otherwise of the project through various financial indices: net present value, internal rate of return and Capital period of reoccupation, benefit cost ratio, analysis of Sensitivity. The methods that were used are the deductive method, the inductive method and the statistical method, which allowed to obtain theoretical information universal and at the same time make the observation of facts and thereby raise a scan using graphics Statisticians. The technique for collecting information were through the implementation of surveys and interviews both plaintiffs, bidders and suppliers. The main results obtained from the research are; per capita consumption averages of 12 boxes per year per family, which acquired the product comes from 25 units to an accessible price of $1.30, likewise prefer to purchase in the supermarkets in the town, it could finally be observed that the m most of the population is willing to the acquisition of this new product ¨infusiones-based cafe¨ pulp. Within the discussion is the study of market where it was established that for the first year there is a potential demand for 629.733 boxes, a real demand of 547.868 boxes and 443.773 boxes effective demand. By means of the balance between supply and demand is estimated a demand unsatisfied 167.533 boxes for the first year. The technical study Palanda province of Zamora Chinchipe sets the size and location of the same company to be located in the canton site which complies with all the factors of location; the installed capacity is equivalent to 66,560 boxes 80% for the first year, the project is estimated for an economic life of 5 years. The financial study points out the budgets required for the production and operation of the company with an investment of $24,587.54 for which a loan of $10,000.00 in the BanEcuador with a 9.76% interest rate will be annual. Finally was the financial evaluation which yielded the following results: net present value of $18,642.00; Internal rate of return of 41.02%; Benefit cost ratio is $1. 19ctv. for every dollar invested, the company wins $0.19 cents. dollar; the period in which the capital recovers is in 3 years, 7 months and 17 days; sensitivity analysis indicating that the project supports an increase in the costs of the 13.50% achieving a coefficient of the 0.98 sensitivity and a decrease in the revenue of the 10.53 a coefficient of sensitivity of the 0.98%, so the project is It is considered feasible for execution, whose conclusions and recommendations thus determine it by attaching itself to the bibliography consulted with their respective annexes.